(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the effectiveness of upper limb rehabilitation combined with repetitive transcranial magnetic stimulation in patients with cerebral infarction. Subjects and methods: This was a prospective, controlled interventional study conducted to assess the outcomes of upper limb rehabilitation combined with in stroke patients treated at the Rehabilitation Center of Bach Mai Hospital from August 2024 to May 2025. The study included 60 patients in the acute and early subacute phases of stroke, selected using a convenient sampling method. Results: After the intervention, upper limb motor function assessed by the action research arm test improved by 9.9 ± 4.3 points, corresponding to a 17.36% (9.9/57) increase. The level of independence in activities of daily living, measured by the Barthel Index, improved by 35 points compared with the control group. This difference was statistically significant (p < 0.05). No adverse effects were reported during the intervention. Conclusion: Repetitive transcranial magnetic stimulation is a safe and effective non-invasive brain stimulation method that enhances upper limb functional recovery and improves quality of life in patients with acute and early subacute cerebral infarction.